Film festivals from European geopolitics to global cinephilia - Valck, Marijke de 1975- (Film culture in transition, 2007)
The film festival has come a long way from its relatively humble origins in Venice in 1932 - when nine nations presented twenty-five feature films screened in an open-air cinema where men had to adhere to standards of formal evening attire. Hugely popular events that attract diverse lovers of cinema worldwide, today's most famous film festivals - Cannes, Berlin, Venice, and Rotterdam - continue the story of a phenomenon that began in the midst of geopolitical disputes in war-torn Europe. Film Festivals shows how these festivals turned impediments into advantages and developed a successful global network that addresses issues as diverse as programming and prizes, national legitimation, city marketing, cinephilia, glamour, and audience. Discussing the festival as a media event and looking closer at various festival visitors, this volume also questions whether 'successful' is in fact the appropriate term for understanding developments that could be considered dogmatic in their insistence on framing filmmakers as auteurs and films as belonging to 'new waves.' An essential title for everyone interested in the culture